Dress to Impress: Public Perception of Plastic Surgeon Attire. (27th November 2021) - Dayani, Fara; Thawanyarat, Kometh; Mirmanesh, Michael; Spargo, Tavish; Saia, Whitney; Nazerali, Rahim
Abstract: Background: Physician attire has been shown to impact patients' perceptions of their provider with regards to professionalism, competency, and trustworthiness in various surgical subspecialties, except in plastic and reconstructive surgery. Objectives: The authors sought to address this knowledge gap and obtain objective information regarding patients' preferences. Methods: A survey was distributed to adult, English-speaking participants in the United States using the Amazon MTurk platform from February 2020 to December 2020. Participants were asked to evaluate with a 5-point Likert scale 6 attires (scrubs, scrubs with white coat, formal attire, formal attire with white coat, casual, casual with white coat) in terms of professionalism, competency, and trustworthiness for male and female plastic surgeons during their first encounter in clinic. Results: A total of 316 responses were obtained from 43.4% men and 56.6% women. The mean age of participants was 53.2 years. The highest scores across all metrics of professionalism, competency, trustworthiness, willingness to share information, confidence in the provider, and confidence in surgical outcomes were given to the formal attire with white coat group, with average scores of 4.85, 4.71, 4.69, 4.73, 4.79, and 4.72, respectively. The lowest scores across all metrics belonged to the casual attire group with scores of 3.36, 3.29, 3.31, 3.39, 3.29, and 3.20, respectively. Patients preferred formal attire for young plastic surgeons ( P  = 0.039). Conclusions: This study suggests that physician attire impacts patients' perception of plastic surgeons regarding their professionalism, competency, and trustworthiness. White coats continue to remain a powerful entity in clinical settings given that attires with white coats were consistently ranked higher.